Pengimarahan Surau dan Musala Sekolah-sekolah Kementerian Pendidikan Malaysia: Suatu Sorotan Terhadap Masalah Pelaksanaan Aktiviti : Enlivening Surau and Musolla at MOE Schools: A Research on Problems During Activity Implementation - Ismail, Mazlan; Yusof, Muhammed (Journal of Al-Falah, 2025)
The enlightenment of the Surau and Musolla of the schools of the Ministry of Education Malaysia (MOE) is a mechanism towards transformation that leads to the formation of students in terms of “Rabbani” who have noble characters and academic excellence. Indeed, the successful execution of da’wah and scholarly programs has shown dedicated collaborative efforts between the superiors and the school. However, what is clearly seen behind an ideal students’ self-development are a few problems that need to be faced by the school administrators, educators and the students themselves. Therefore, the purpose of this article is to investigate the problems that happen during the implementation of the activities. This study uses library and field research methods. In the field research, interview techniques, observations, and documentation had been employed to obtain data. Descriptive studies have been conducted to enable researchers to get a superficial picture of a phenomenon. Researchers’ findings show that the problem in the execution of the program to enlighten the Surau and Musolla in the category of aspiring schools is related to financial and time constraints, a lack of cooperation among the teachers, a shortage of support from external parties, a deficiency in teamwork within students, and the measurement level of enlightenment.